PENCIPTAAN DESAIN MOTIF BATIK SIDOARJO PADA SYAL DENGAN SUMBER IDE CANDI DERMO - Aissyah Febi Alamanda Hurrin; Deny Arifiana (BAJU: Journal of Fashion and Textile Design Unesa, 2025)
Abstract The design of batik is one of stages in batik making process. The development of motif ideas can create patterns and motifs on batik fabric. The making of batik decorative motif design in this study is inspired by cultural heritage found in Sidoarjo. This research an art based study that describes the batik motif design from Sidoarjo, this research also inspired by Dermo Temple. The objective of this research are: (1) To describe the process of exploring the Sidoarjo Batik motif with the source of the idea of Dermo Temple which will be applied to products in the form of scarves.  (2) to describe the process of creating Sidoarjo batik design inspired by the Dermo temple to be applied to a product in form of scarf. (3) to describe the final result of the Sidoarjo batik design creation inspired by Dermo Temple to be applied to a product in form of scarf. The method used in this research is the artwork creation, that’s consist four stages: exploration or pre design, design development, realization of the work, and also the presentation of the work. At the design stage of the work, alternative designs are made, so that 3 motif designs can be selected that will be applied to products in the form of scarves. The results of the creation stated that the scarf product measuring 35 cm x 180 cm was created according to the characteristics of the Batik Sidoarjo and Dermo Temple motifs. The results of the creation state that the scarf product measuring 35 cm x 180 cm was created according to the characteristics of the Batik motif of Sidoarjo and Dermo Temple as the main motif of batik. The results of the creation state that: (1) Scarf products measuring 35 cm x 180 cm were created according to the characteristics of the Batik motifs of Sidoarjo and Dermo Temple as the main motif of batik. (2 The motifs created on the product in the form of scarves go through the design development stage, so that batik patterns can be created in accordance with the results of the motif exploration. (3) The finished product is in the form of a scarf created with the written batik technique.